Sensitivity of CT, MRI, and EUS-FNA/B in the preoperative workup of histologically proven left-sided pancreatic lesions - Gorris, Myrte; Janssen, Quisette P.; Besselink, Marc G.; van den Broek, Bram L.J.; van Eijck, Casper H.J.; van Gils, Marjon J.; Koerkamp, Bas Groot; Struik, Femke; van Driel, Lydi M.J.W.; van Hooft, Jeanin E. (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.], 2022)
Left-sided pancreatic lesions are often treated surgically. Accurate diagnostic work-up is therefore essential to prevent futile major abdominal surgery. Large series focusing specifically on the preoperative work-up of left-sided pancreatic lesions are lacking. This surgical cohort analysis describes the sensitivity of CT, MRI, and EUS-FNA/B in the diagnostic work-up of left-sided pancreatic lesions. We performed a post-hoc analysis of patients who underwent surgery for a left-sided pancreatic lesion between April 2010 and August 2017 and participated in the randomized CPR trial. Primary outcome was the sensitivity of CT, MRI, and EUS-FNA/B. Sensitivity was determined as the most likely diagnosis of each modality compared with the postoperative histopathological diagnosis. Additionally, the change in sensitivity of EUS versus EUS-FNA/B (i.e., cyst fluid analysis, and/or tissue acquisition) was measured. Overall, 181 patients were included (benign: 23%, premalignant: 27%, malignant: 50%). Most patients had solid lesions (65%). Preoperative imaging included CT (86%), MRI (41%), EUS (68%). Overall, CT and EUS-FNA/B reached a sensitivity of both 71%, compared with 66% for MRI. When EUS was combined with FNA/B, sensitivity rose from 64% to 71%. For solid lesions, CT reached the highest sensitivity (75%) when compared with MRI (70%) and EUS-FNA/B (69%). For cystic lesions, EUS-FNA/B reached the highest sensitivity (75%) when compared with CT and MRI (both 62%). CT is the most sensitive diagnostic modality for solid and EUS-FNA/B for cystic left-sided pancreatic lesions. EUS-FNA/B was associated with an increased sensitivity when compared to EUS alone.